2010
DOI: 10.20473/jmtt.v3i2.2396
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat Kepatuhan Wajib Pajak Dan Tarif Pajak: Uji Pengaruh Karakteristik Pendapatan

Abstract: The research was intended to investigate the relationship between tax tariff and the compliance of tax payer; and how this relationship was affected by type of income (endowed income vs earned income). The degree of the tax payer compliance was measured based on reported income. The treatment of the experiment was conducted in accordance with variables of reported income (endowed v.s. earned income) and variables of tax tariff (15% vs 30%). The testing results on the impact of endowed income towards the degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Najah ( 2008) and Husaini, Pirzada, and Saiful (2020) argues that there is no difference in corporate taxpayers' compliance levels before and after the enactment of a tax audit. Komalasari and Nasih (2010) tested the influence of taxpayers' reported income toward the level of their compliance and found that there was no significant difference in the level of taxpayer compliance whether a 15% or 30% tax tariff was imposed. Fajarwati, Kertahadi, and Kurniawan ( 2004) conducted a study in several tax offices in Malang Raya, East Java and found that there was a significant difference between the degrees of tax compliance before and after the implementation of a tax modernization program.…”
Section: Differences In Taxpayers' Compliance Levelsmentioning
confidence: 99%
“…Najah ( 2008) and Husaini, Pirzada, and Saiful (2020) argues that there is no difference in corporate taxpayers' compliance levels before and after the enactment of a tax audit. Komalasari and Nasih (2010) tested the influence of taxpayers' reported income toward the level of their compliance and found that there was no significant difference in the level of taxpayer compliance whether a 15% or 30% tax tariff was imposed. Fajarwati, Kertahadi, and Kurniawan ( 2004) conducted a study in several tax offices in Malang Raya, East Java and found that there was a significant difference between the degrees of tax compliance before and after the implementation of a tax modernization program.…”
Section: Differences In Taxpayers' Compliance Levelsmentioning
confidence: 99%